Macroeconomic consequences of distributional conflicts - Andreas Schäfer; Thomas M. Steger (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper aims at better understanding the inefficiency due to distributional conflicts, which are inherent in every market economy. To this end, we set up a simple general equilibrium model with the following characteristics: two groups of agents (capitalists and workers), an endogenous income tax, productive government expenditures, social transfers, and an outside option for capital. The political mechanism employed in this paper accounts for the evidence showing that the degree of organization of major interest groups has an impact on political outcomes and, in addition, allows for strategic interaction among major interest groups. We decompose the overall inefficiency into three components: (i) a fundamental time inconsistency problem; (ii) strategic interaction in the political process; (iii) heterogeneity among individuals and the resulting unavoidable conflict of interest. A numerical exercise (based on OECD data) shows that the distributional-conflict inefficiency may cause a substantial output loss of about 7%.
Keywords: E6; H2; O4; 330; Verteilungskonflikt; Klassenkampf; Zeitkonsistenz; Wirtschaftliche Effizienz; Makroökonomischer Einfluss; Theorie; OECD-Staaten